Effectiveness of Emotional Freedom Techniques (EFT) and Aromatherapy Oils in Reducing Anxiety in Third Trimester Pregnant Women - Karnilan Lestari Ningsi Sam (GLOBAL HEALTH SCIENCE GROUP, 2025)
Studies show that the global incidence of anxiety is 23% in Alberta, Canada, 15,6% in Germany, and 49% in Pakistan. Anxiety in pregnancy is related to depression which affects the mother and baby, besides that it can pose risks to the mother's mental health such as increasing the risk of depression after giving birth. Objective: to find out the Effectiveness of Emotional Freedom Techniques (EFT) and Aromatherapy Oils in Reducing Anxiety in Third Trimester Pregnant Women. Method: using the true experimental design method using one group design, pre test-post test design, sampling technique using purposive sampling. Pregnant women will have their Anxiety scale measured using the State Anxiety Invantory Score (STAI), data analysis is carried out univariately to describe the frequency distribution and bivariately using the Wilcoxon test. Results: The average anxiety score for the Pre Test was 2,31 and the Post Test was 1,31. The results of the Wilcoxon signed rank test statistic show that the value is ρ < 0,001. Conclusions: The effectiveness of Emotional Freedom Techniques (EFT) and aromatherapy oils based on the Wilcoxon signed rank test statistical test can be seen with a value of ρ < 0,001, which means it is proven to reduce anxiety in third trimester pregnant women.